Encyclopedia of Inorganic and Bioinorganic Chemistry 2020
DOI: 10.1002/9781119951438.eibc2717
|View full text |Cite
|
Sign up to set email alerts
|

Poly(aminoborane)s and Poly(iminoborane)s

Abstract: The field of so‐called inorganic polymers has seen significant advances in recent years. Poly(aminoborane)s and poly(iminoborane)s represent examples for compounds of this type, possessing a polymer main chain that exclusively contains boron and nitrogen. These structures are of fundamental and application‐oriented interest in the context of BN/CC isosterism. This article summarizes the historic background, properties, synthetic aspects as well as new developments in the fields of poly(aminoborane)s and poly(i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 137 publications
0
5
0
Order By: Relevance
“…Boron-containing macromolecular materials are attracting considerable current research interest. While polymers having the vacant p-orbital of trivalent boron incorporated in a π-conjugated backbone have been used for electronic, optoelectronic, and sensory applications, various boronic acid-based polymers are noted for their well-established biomedical activities. , The incorporation of BN units into organic molecules or polymers to replace selected isoelectronic and isosteric CC units has evolved into a viable approach for accessing materials with special properties and functions. Some of us recently reported a series of BN-doped inorganic–organic hybrid polymers, including BN analogs of poly­(phenylenevinylene) , (PPV) and poly­(thiophene vinylene) (PTV). In a collaborative effort with the Pich group, borazine-based hybrid cyclomatrix polymers with a dapsone-type diaryl sulfone as a building block were prepared that self-assemble into microspheres .…”
Section: Introductionmentioning
confidence: 99%
“…Boron-containing macromolecular materials are attracting considerable current research interest. While polymers having the vacant p-orbital of trivalent boron incorporated in a π-conjugated backbone have been used for electronic, optoelectronic, and sensory applications, various boronic acid-based polymers are noted for their well-established biomedical activities. , The incorporation of BN units into organic molecules or polymers to replace selected isoelectronic and isosteric CC units has evolved into a viable approach for accessing materials with special properties and functions. Some of us recently reported a series of BN-doped inorganic–organic hybrid polymers, including BN analogs of poly­(phenylenevinylene) , (PPV) and poly­(thiophene vinylene) (PTV). In a collaborative effort with the Pich group, borazine-based hybrid cyclomatrix polymers with a dapsone-type diaryl sulfone as a building block were prepared that self-assemble into microspheres .…”
Section: Introductionmentioning
confidence: 99%
“…[3] This so-called outer-sphere substrate activation has been demonstrated for a wide variety of substrates, including amine boranes H 3 B•NMe n H 3-n (n = 0-2), commonly referred to as isoelectronic main group analogues of alkanes with great potential for the construction of oligomeric, polymeric and heterogeneous BÀ N materials. [4,5] The iron complex [Fe(N(CH 2 CH 2 PiPr 2 ) 2 )(H)(CO)], often studied for organic transformations, is an excellent precatalyst for the dehydropolymerisation of ammonia borane, H 3 B•NH 3 , [6] its singly methylated analogue H 3 B•NMeH 2 , silyl functionalised derivatives, and hydrazine borane (Figure 1a). [7] Recently, Weller and co-workers showed that the same aliphatic PN(H)P pincer ligand NH(CH 2 CH 2 PiPr 2 ) 2 forms a highly active and air-tolerant cationic Rh I precatalyst that can be used for the production of processable poly(aminoborane)s from H 3 B•NMeH 2 on scale (Fig-ure 1a).…”
Section: Introductionmentioning
confidence: 99%
“…Catalytic dehydrocoupling reactions of amine–boranes, RR′HN–BH 2 R′′, first demonstrated by Manners and co-workers, 7 leads to B–N catenated products of the form [RR′N–BHR′′] x / n , which are either ring systems, linear oligomers, or polymers (Scheme 1i). 2,7–9 Catalytic or initiated transformations of their unsaturated congeners, aminoboranes, RXNBR′Y, have not been systematically explored thus far. Paetzold and co-workers extensively explored the generation of iminoboranes, RNBR′, through thermolysis of suitable molecular precursors (including N -silyl- B -chloro-aminoboranes), and studied their follow-up chemistry (Scheme 1ii).…”
mentioning
confidence: 99%
“…In this way, we accomplished the preparation of well-defined cyclolinear BN catenated species (Scheme 1iii), which represent the closest approach to poly(iminoborane)s to date. 8 e ,15…”
mentioning
confidence: 99%